Drunk driving preventation system with ignition lock & IOT / Sarah Shipun Anuar - Shipun Anuar, Sarah (2024)
Driving under the influence of alcohol are harmful for society. This kind of behaviour can cause a lot of damage which surely effect many people, physically and psychologically. This behaviour also increases the road accidents that occur each year. A prototype of drunk driving preventation system will be build that will help drunk driver’s attempt driving while under influence of a alcohol. In this prototype will be used LCD, LED, Microcontroller Arduino UNO and esp-32, alcohol sensor MQ-03and buzzer. This system will operate as such the car ignition will remain off after alcohol sensor detect a high level of Blood Alcohol Content (BAC) in the user breath and send information to microcontroller and microcontroller will communicate with Blynk server and send notification to user’s relative toward Telegram. This system can be useful in enforcing legal alcohol limit